PREPARATION AND CHARACTERIZATION OF HYDROXYPROPYL METHYLCELLULOSE PRODUCED FROM α-CELLULOSE BETUNG BAMBOO (DENDROCALAMUS ASPER) AND IT’S EVALUATION ON GEL FORMULATION - AKBAR, MUHAMMAD HERPI; HARMITA; SURYADI, HERMAN (International Journal of Pharmacy and Pharmaceutical Sciences, 2020)
Objective: This study aim to obtain the optimum condition of preparation of hydroxypropyl methylcellulose (HPMC) produced from α-cellulose betung bamboo, physicochemical properties of HPMC powder and its characteristics in a gel formulation. Methods: HPMC of betung bamboo (HPMC BB) were optimized by central composite design (CCD) using three variables (sodium hydroxide concentration, dimethyl sulfate concentration, and temperature) and five levels (0,±1, and±α). The suggested optimum condition was subjected to further characterization. HPMC BB was characterized using Fourier transform infrared (FTIR) spectrometry, particle size analyzer (PSA), x-ray diffraction (XRD), scanning electron microscope (SEM) and compared to HPMC 60SH as the reference. Then, HPMC BB was used as a gelling agent in a gel formulation and the gel was evaluated, including appearance and homogeneity, pH, viscosity, and spreadability. Results: Optimum condition of preparation of HPMC BB was using sodium hydroxide 27.68% (w/v) and 1.26 ml dimethyl sulfate (based on 1 g α-cellulose) at 58.11 °C which resulted in molar substitution 0.21 and degree of substitution 2.09. The results showed that HPMC BB was a fine powder with yellowish-white color, odorless and tasteless, pH 7.02, residue on ignition 1.39%, methoxy groups content 28.56%, hydroxypropoxy groups content 7.09%, mean particle size 98.595 μm, loss on drying 3.62%, and moisture content 7.47%. Flow properties of HPMC BB classified in the fair category. The infrared spectrum and diffraction patterns were relatively similar to HPMC 60SH. The gel has a good homogeneity and spreadability and viscosity 142.5 mPa⋅s. pH 6.37. Conclusion: Based on the comparison to reference, HPMC BB showed relatively similar physicochemical and powder properties. However, HPMC BB is not recommended as a gelling agent in gel formulation because it has a low viscosity.